2011
DOI: 10.1007/s00464-011-2055-9
|View full text |Cite
|
Sign up to set email alerts
|

3D HD versus 2D HD: surgical task efficiency in standardised phantom tasks

Abstract: This study shows that 3D HD using a state-of-the-art 3D monitor permits superior task efficiency, even as compared with the latest 2D HD video systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
135
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(143 citation statements)
references
References 17 publications
4
135
1
3
Order By: Relevance
“…During the SILS, frequent movement of camera scope is more limited compared to conventional multiport laparoscopic surgery because of collision of instruments. Recently developed 3D scope system could be useful in terms of superior task efficiency because it can show more effective perspective and depth of field to operator, which means the decreased number of "air-catching" and less position change of camera scope (29)(30)(31). Secondly, the length and shape of instrument can be chosen depending on the situation.…”
Section: Prerequisitesmentioning
confidence: 99%
“…During the SILS, frequent movement of camera scope is more limited compared to conventional multiport laparoscopic surgery because of collision of instruments. Recently developed 3D scope system could be useful in terms of superior task efficiency because it can show more effective perspective and depth of field to operator, which means the decreased number of "air-catching" and less position change of camera scope (29)(30)(31). Secondly, the length and shape of instrument can be chosen depending on the situation.…”
Section: Prerequisitesmentioning
confidence: 99%
“…Some studies have proven that very experienced surgeons can compensate for the lack of stereo perception inherent in 2D systems 7, 8. Nevertheless, several studies have shown that 3D endoscopic systems are superior to 2D systems, especially when involving complex operations, and for less experienced surgeons 6, 9, 10, 11, 12, 13. Our surgeon reported that the 3D system provides a better sense of depth, which can facilitate precise tasks, such as suturing.…”
Section: Discussionmentioning
confidence: 77%
“…The same surgeon, who was experienced in 2D VATS lobectomy, but relatively less experienced in the use of 3D systems, performed all operations. Because of his extensive experience, the surgeon could compensate for the limitations of the 2D system by using 2D cues, such as light and shade, the relative size and position of tissues and organs, texture gradient, spatial perspective, and motion parallax 6. Some studies have proven that very experienced surgeons can compensate for the lack of stereo perception inherent in 2D systems 7, 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robotic systems such as the 'da Vinci' offer several advantages when compared to standard laparoscopy including: (i) increased fine manual dexterity with motion scaling and tremor stabilisation; (ii) improved ergonomic position, aiding the surgeons' comfort by allowing them to operate from a seated position and (iii) improved visualization with image stereopsis (Kwok, et al, 2012;Rockall and Darzi, 2003). The benefit of the three-dimensional video-imaging systems in MIS has been proved under different experimental conditions (e.g., (Kong, Oh et al 2010;Storz, et al 2012)). The main drawbacks of the Da Vinci system are its high cost and the high training required to the surgeons to use this device.…”
mentioning
confidence: 99%